ANALISIS PEMASARAN KOSMETIK ILEGAL YANG TIDAK TERDAFTAR PADA BPOM BERDASARKAN UNDANG-UNDANG NOMOR 8 TENTANG PERLINDUNGAN KONSUMEN (Contoh Kasus: Pabrik Skala Rumahan Di Kalideres Tahun 2019) - Dinda Maulida; Jeane Neltje Saly (Jurnal Hukum Adigama, 2022)
Consumer protection is regulated in Law no. 8 of 1999 concerning Consumer Protection. Article 7letter a contains that business actors must have good intentions in their business activities, withthe aim of protecting consumers, but this has not been achieved optimally. the content and contentcontained in the product cannot be accounted for because there is no certainty from the expertiseof the product, such as the absence of a halal label. does not meet the standards according tolegislation, does not comply with quality standards, cosmetic products do not comply with theprovisions. Therefore, there are many dangerous cosmetic products circulating in the market dueto the lack of supervision from related parties. This research uses normative legal researchmethods. The results of the study indicate that the rights of consumers who are harmed and arestill not fulfilled based on Law no. 8 of 1999 concerning Consumer Protection and is still notef ective because of the supervision carried out by BPOM in overcoming the problem of illegalcosmetics.